Semantic Interoperability to support context in adaptive applications - WADE, VINCENT PATRICK (IEEE, 2008)
The challenge of supporting Ubiquitous Computing is to assist the user by helping their applications make better decisions with better information. Smart spaces and other information sources can provide this information, but it is unrealistic to expect all the information to be represented in the same way everywhere. This means that the goal of ubiquitous computing translates into a problem of information integration. This paper presents a new knowledge-driven approach to applying contextual information to user applications. The objective of the design is to use a semantic integration, represented in topic maps, to deliver knowledge found in available services to personalise and improve the functionality of an integrated application. A brief discussion of the different semantic technologies employed in the system is followed by a presentation of the architecture of the system and its novel combination of semantic technologies. Two Use Cases are discussed, one specifically related to Ubiquitous Environments. Finally, the work is related to other research in the areas of Semantic Mediation and Context Awareness.
PUBLISHED
Keywords: Computer Science